A garbage can model for Schumpeterian process: the network effects. (19th March 2008) - Wu, Shu-Yuan; Brabazon, Anthony K.
Through interactive learning activities of technology based entrepreneurs and their potential customers, novel combinations of technology components are developed into vehicles of customer values. This study treats technological possibilities and customers' latent needs as the dimensions of an inter organisational Garbage-Can space, inside of which learning agents from the demand and supply sides interact. It simulates an ongoing Schumpeterian process ('creative destruction') to investigate the influences of social network, boundary-spanning organisations and demand-side innovativeness.